Minimum record length for detecting a prospective uniform sea level acceleration at a tide gauge station. Issue 1 (31st December 2022) - Iz, H. Bâki; Shum, C. K.
ABSTRACT: The unambiguous detection of a uniform sea level acceleration at a tide gauge station is important under an increasingly warmer Earth for the long-term coastal risk assessments. Although the timescales needed for detecting mean sea level trends at tide gauges were well investigated in the past, very few studies addressed the same issue for the sea level accelerations in depth. In this study, we demonstrate that the ability to discern a uniform sea level acceleration at a tide gauge station depends on its magnitude, systematic and random sea level variations, the degree of autocorrelation of the random variations, the length of its historical record and the desired statistical significance level of its estimate. We offer a formulary to estimate the required minimum record lengths needed to detect a statistically significant prospective uniform acceleration at a coastal or Island tide gauge station based on the retrospective analyses of its sea level record. To demonstrate its effectiveness, the minimum record lengths required to detect statistically significant prospective uniform accelerations were calculated at 19 globally distributed tide gauge stations with long records.